Biomass conversion into activated carbon as a sustainable energy material for the development of supercapacitor devices. Issue 2 (15th June 2022) - Awitdrus, Awitdrus; Yusra, Deris Afdal; Taer, Erman; Agustino, Agustino; Apriwandi, Apriwandi; Farma, Rakhmawati; Taslim, Rika
ABSTRACT: To address current energy consumption and chemical production, biomass is a promising alternative that can be used as an inexpensive and sustainable energy material for the development of supercapacitor devices. In this study, the jackfruit peel (JP) waste is used for the synthesis of an inexpensive and eco-friendly activated carbon (AC) as a sustainable energy material for the development of supercapacitor devices. JP wastes were synthesized by three-step approach consisting of KOH activation via nitrogen carbonization at 600°C and CO2 activation at different temperatures (850, 900, and 950°C). The specific capacitances of supercapacitor cells are 85 F g −1, 191 F g −1, and 131 F g −1 for the JP-850, JP-900, and JP-950, respectively. Based on the results, the JP samples are suitable to be developed as an inexpensive and eco-friendly AC for electrode material in supercapacitor applications due to their good physicochemical properties and electrochemical performance.